2020
DOI: 10.1038/s41467-019-14004-5
|View full text |Cite
|
Sign up to set email alerts
|

Irp2 regulates insulin production through iron-mediated Cdkal1-catalyzed tRNA modification

Abstract: Regulation of cellular iron homeostasis is crucial as both iron excess and deficiency cause hematological and neurodegenerative diseases. Here we show that mice lacking ironregulatory protein 2 (Irp2), a regulator of cellular iron homeostasis, develop diabetes. Irp2 post-transcriptionally regulates the iron-uptake protein transferrin receptor 1 (TfR1) and the iron-storage protein ferritin, and dysregulation of these proteins due to Irp2 loss causes functional iron deficiency in β cells. This impairs Fe-S clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 68 publications
1
48
0
Order By: Relevance
“…Distinct requirements for iron in beta cells have not been demonstrated unequivocally but could already be inferred from their high ferritin expression in both mouse [ 33 ] and human [ 28 ]. Additionally, mice lacking IREB2, an RNA-binding protein that regulates intracellular iron levels by modulating the translation and stability of Tfrc , Ftl1 , and Fth1 (the latter two encoding the light and heavy chains that comprise ferritin), were recently found to display a specific functional iron deficiency in beta cells resulting in impaired proinsulin processing and hence in reduced insulin content and secretion [ 34 ]. This study revealed a crucial role of iron for beta cell function that is further supported by our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct requirements for iron in beta cells have not been demonstrated unequivocally but could already be inferred from their high ferritin expression in both mouse [ 33 ] and human [ 28 ]. Additionally, mice lacking IREB2, an RNA-binding protein that regulates intracellular iron levels by modulating the translation and stability of Tfrc , Ftl1 , and Fth1 (the latter two encoding the light and heavy chains that comprise ferritin), were recently found to display a specific functional iron deficiency in beta cells resulting in impaired proinsulin processing and hence in reduced insulin content and secretion [ 34 ]. This study revealed a crucial role of iron for beta cell function that is further supported by our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Irp2-/- mice develop microcytic anemia [ 127 , 128 ] and age-dependent neurological defects with variable penetrance [ 129 , 130 , 131 , 132 ]. Recent data suggested that these animals also exhibit glucose intolerance and develop diabetes [ 133 ]. This phenotype is caused by functional iron deficiency in pancreatic β cells due to reduced TfR1 expression and excessive ferritin accumulation as a result of IRP2 ablation.…”
Section: Irp2 and Glucose Metabolismmentioning
confidence: 99%
“…Another recent study demonstrated that functional iron deficiency in pancreatic β-cells leads to impaired insulin production and development of diabetes. 50 Finally, it was reported that progressive nutritional maternal iron deficiency during pregnancy prioritizes appropriate placental iron homeostasis at the costs of fetal iron status. 51 The authors propose that such a mechanism protects the pregnancy from detrimental placental dysfunction.…”
Section: Cellular Iron Acquisition Utilization and Storagementioning
confidence: 99%
“…104,105 Recently, deficiency of Irp2 was linked to impaired insulin production by pancreatic β-cells, as mentioned above. 50 Of note, the lack of similarities between mouse models lacking either Irp1 or Irp2 might be explained by the differential impact of tissue oxygen levels on their functionality. 106 In contrast to single Irp1 KO mice that show iron hyperabsorption in the gut, intestine-specific ablation of both IRPs in adulthood, both constitutive and ligand-induced, blocked iron acquisition from the diet.…”
Section: Cellular Iron Handing By Ire/irp Regulatory Mechanisms -Cementioning
confidence: 99%